MAC protocol for indoor optical wireless networks. Issue 19 (1st December 2019) - Edirisinghe, Sampath; Lim, Christina; Nirmalathas, Ampalavanapillai; Wong, Elaine; Ranaweera, Chathurika; Wang, Ke; Alameh, Kamal
Abstract : Optical wireless communication has emerged as a promising candidate for future high data rate indoor applications such as virtual reality. Even though physical layer of optical wireless networks has rapidly developed during last decade, upper layer architecture that harness the physical layer capabilities has not yet been developed in the same pace. To this end, the authors develop a novel contention‐based medium access control (MAC) protocol that accompanies a service differentiation mechanism and a dynamic contention window tuning algorithm. The proposed service differentiation mechanism can identify the diverse traffic types and facilitate their throughput and delay requirements. To add more robustness to the contention‐based MAC protocol which depends on contention windows to avoid collisions, the authors also propose an algorithm that dynamically changes the contention window sizes to suit the congestion level. They analyse the performance of the proposed MAC protocol under diverse network configurations and they show that it is far more effective to use end‐user network metrics such as throughput in dynamic adaptation algorithms in addition to collision rate due to the wide range of traffic types present in the network. The proposed results demonstrate that the proposed MAC protocol can handle next‐generation traffic types and their stringent latency requirements in an effective manner.